Study on Shenbao Tablet in Treating Kidney-yang Deficiency Syndrome-based on Metabolomics - Zhou, Qing-gang; Han, Bao-xia; Yi, Huan; Geng, Zhao; Gou, Xiao-jun (Combinatorial Chemistry & High Throughput Screening, 2025)
AimThe aim of this study was to elucidate the mechanism of action of Shenbao tablets using metabolomics approach.BackgroundKidney-yang deficiency is a common syndrome type in traditional Chinese Medicine (TCM) syndrome typology, closely related to disorders of multiple metabolic pathways and is the root cause and underlying syndrome type of many diseases. Shenbao tablets can significantly improve the main symptoms of kidney yang deficiency syndrome, but the mechanism of action of Shenbao tablets on kidney yang deficiency syndrome is still unknown.MethodsThe rats were intraperitoneally injected with hydrocortisone once a day for 40 days to simulate the syndrome. Traditional pharmacodynamic indicators (body mass, biochemical indicators and pathology) were used to evaluate the efficacy of the medicine. Serum, urine and feces were collected from rats. UPLC/MS metabolomics method was used to study the overall metabolic profile of serum, while GC/MS metabolomics method was used to study the metabolic spectrum of urine and feces.ResultsResults showed that the syndrome was significantly improved in the treatment group, and obvious metabolic disorders were observed in rats with the syndrome, with 47 potential biomarkers identified. Pathway analysis showed that nicotinate and nicotinamide metabolism, glycine, serine and trione metabolism, aminoacyl tRNA biosynthesis, glycoxylate and dicarboxylate metabolism were the major ways for Shenbao tablet to improve kidney-yang deficiency syndrome.ConclusionThe mechanism of action of Shenbao tablet in improving the syndrome involves the regulation of energy metabolism, amino acid metabolism, bile acid metabolism, fatty acid metabolism and intestinal microorganisms. This work shows that metabolomics is a promising tool for studying the essence of syndrome theory in TCM and the mechanisms of TCM.
Keywords: metabolomics